Faculty of Information Management students' as an information ambassador / Nor Atilia Shuhaimi and Nurul Hidayah Johari - Shuhaimi, Nor Atilia; Johari, Nurul Hidayah (Faculty of Information Management, 2015)
"This article is discussing about how Information Management Students' as an information ambassador. This article also discussing about the characteristics needed to be an information ambassador. There also a discussion about the roles and responsibilities in carried out the job as information ambassador. In this article, it also discusses about what course that being offered to the students of information management."